Information security 13th International Conference, ISC 2010, Boca Raton, FL, USA, October 25-28, 2010: revised selected papers - Burmester, Mike; Tsudik, Gene; Magliveras, Spyros; Ilic, Ivana (Lecture notes in computer science, 2011)
aThis book constitutes the refereed proceedings of the 13th International Conference on Information Security, ISC 2010, held in Boca Raton, FL, USA, in October 2010. The 25 revised full papers and the 11 short papers presented were carefully reviewed and selected from 117 submissions. The papers are organized in topical sections on attacks and analysis; analysis; authentication, PIR and content identification; privacy; malware, crimeware and code injection; intrusion detection; side channels; cryptography; smartphones; biometrics; cryptography, application; buffer overflow; and cryptography, theory.